Clinical findings in a patient with FARS2 mutations and early‐infantile‐encephalopathy with epilepsy. Issue 11 (23rd August 2016) - Raviglione, Federico; Conte, Giorgio; Ghezzi, Daniele; Parazzini, Cecilia; Righini, Andrea; Vergaro, Raffaella; Legati, Andrea; Spaccini, Luigina; Gasperini, Serena; Garavaglia, Barbara; Mastrangelo, Massimo
Abstract : The FARS2 gene encodes the mitochondrial phenylalanyl‐tRNA synthetase and is implicated in autosomal recessive combined oxidative phosphorylation deficiency 14, a clinical condition characterized by infantile onset epilepsy and encephalopathy. Mutations in FARS2 have been reported in only few patients, but a detailed description of seizures, electroencephalographic patterns, magnetic resonance imaging findings, and long‐term follow‐up is still needed. We provide a clinical report of a child with FARS2 ‐related disease manifesting drug‐resistant infantile spasms associated with focal seizures. By comparative genomic hybridization analysis we identified a heterozygous microdeletion in the short arm of chromosome 6, inherited from the mother, that encompasses the first coding exon of FARS2 . By sequencing of the FARS2 gene we identified a variant c.1156C>G; p.(R386G), inherited from the father. By using standard spectrophotometric techniques in skin fibroblasts, we found a combined abnormality of complexes I and IV of the mitochondrial respiratory chain. The main clinical features of the patient included axial hypotonia, mild distal hypertonia, and psychomotor delay. The magnetic resonance imaging showed microcephaly, frontal cerebral atrophy, and signal changes of dentate nuclei. At the age of 3 years and 6 months, the patient was still under treatment with vigabatrin and he has been seizure free for the last 23 months. © 2016 Wiley Periodicals, Inc.